Temporal validation of the MMCD score to predict kidney replacement therapy and in-hospital mortality in COVID-19 patients - das Graças José Ventura, Vanessa; Pereira, Polianna Delfino; Pires, Magda Carvalho; Asevedo, Alisson Alves; de Oliveira Jorge, Alzira; dos Santos, Ana Carolina Pitanga; de Moura Costa, André Soares; dos Reis Gomes, Angélica Gomides; Lima, Beatriz Figueiredo; Pessoa, Bruno Porto; Cimini, Christiane Corrêa Rodrigues; de Andrade, Claudio Moisés Valiense; et al. (Springer Nature, 2023)
Background: Acute kidney injury has been described as a common complication in patients hospitalized with COVID-19, which may lead to the need for kidney replacement therapy (KRT) in its most severe forms. Our group developed and validated the MMCD score in Brazilian COVID-19 patients to predict KRT, which showed excellent performance using data from 2020. This study aimed to validate the MMCD score in a large cohort of patients hospitalized with COVID-19 in a different pandemic phase and assess its performance to predict in-hospital mortality. Methods: This study is part of the “Brazilian COVID-19 Registry”, a retrospective observational cohort of consecutive patients hospitalized for laboratory-confirmed COVID-19 in 25 Brazilian hospitals between March 2021 and August 2022. The primary outcome was KRT during hospitalization and the secondary was in-hospital mortality. We also searched literature for other prediction models for KRT, to assess the results in our database. Performance was assessed using area under the receiving operator characteristic curve (AUROC) and the Brier score. Results: A total of 9422 patients were included, 53.8% were men, with a median age of 59 (IQR 48–70) years old. The incidence of KRT was 8.8% and in-hospital mortality was 18.1%. The MMCD score had excellent discrimination and overall performance to predict KRT (AUROC: 0.916 [95% CI 0.909–0.924]; Brier score = 0.057). Despite the excellent discrimination and overall performance (AUROC: 0.922 [95% CI 0.914–0.929]; Brier score = 0.100), the calibration was not satisfactory concerning in-hospital mortality. A random forest model was applied in the database, with inferior performance to predict KRT requirement (AUROC: 0.71 [95% CI 0.69–0.73]). Conclusion: The MMCD score is not appropriate for in-hospital mortality but demonstrates an excellent predictive ability to predict KRT in COVID-19 patients. The instrument is low cost, objective, fast and accurate, and can contribute to supporting clinical decisions in the efficient allocation of assistance resources in patients with COVID-19.
Keywords: Acute kidney injury; COVID-19; Kidney replacement therapy; Mortality; Risk prediction; Score predictive